Application of nanoparticles in cancer detection by Raman scattering based techniques. (1st January 2018) - Ravanshad, Rouhallah; Karimi Zadeh, Ayoob; Amani, Ali Mohammad; Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Savar Dashtaki, Amir; Mirzaei, Esmail; Zare, Bijan
ABSTRACT: In vitro detection technique Raman spectroscopy (Rs), in one number times another Rs  based expert ways of art and so on, are useful instruments for cancer  discovery. top gave greater value to Raman spectroscopy  sers is a relatively new careful way for in vitro  and in vivo discovery that takes away bad points of simple Raman spectroscopy (Rs). Raman spectroscopy (RS) and in particular, multiple RS-based techniques are useful for cancer detection. Surface enhanced Raman spectroscopy (SERS) is a relatively new method for both in vitro and in vivo detection, which eliminates the drawbacks of simple RS. Using nanoparticles has elevated the sensitivity and specificity of SERS. SERS has the potential to increase sensitivity, specificity and spatial resolution in cancer detection, especially in cooperation with other diagnostic imaging tools such as magnetic resonance imaging (MRI) and PET-scan polyethylene terephthalate. Developing a hand held instrument for detecting cancer or other illnesses may also be feasible by using SERS. Frequently, novel nanoparticles are used in SERS. With a focus on nanoparticle utilization, we review the benefits of RS in cancer detection and related biomarkers. With a focus on nanoparticles utilizations, the benefits of RS in cancer detection and related biomarkers were reviewed. In addition, Raman applications to detect some of prevalent were discussed. Also more investigated cancers such as breast and colorectal cancer, multiple nanostructures and their possible special biomarkers, especially as SERS nano-tag have been reviewed. The main purpose of this article is introducing of most popular nanotechnological approaches in cancer detection by using Raman techniques. Moreover, have been caught up on detection and reviewed some of the most prevalent and also more investigated cancers such as breast, colorectal cancer, multiple intriguing nanostructures, especially as SERS nano-tag, special cancer biomarkers and related approaches. The main purpose of this article is to introduce the most popular nanotechnological approaches in cancer detection by using Raman techniques.